Excessive Judicial Deference as Rule of Law Backsliding: When National Security and Effective Rights Protection Collide - Rumyana van Ark; Tarik Gherbaoui (Utrecht Law Review)
In recent years, both domestic and international courts have become increasingly deferential to the executive in cases that concern matters of national security. This trend has resulted in rule of law backsliding and the inadequate and ineffective protection of the human rights of individuals. With the steady rise of populism and politics of fear and division, the threat of insecurity has been hyperinflated and exploited to justify national security measures. The normalisation of this ‘securitisation populism’ has had a profound impact on human right values, tolerance, and the rule of law. Through an analysis of illustrative case law of the European Court of Human Rights as well as domestic courts in the United Kingdom, this article focuses on the role which supranational human rights courts such as the ECtHR should play in putting (early) breaks on rule of law backsliding at the domestic level. The article concludes that it is in the long-term public interest to establish strong rule of law and human rights safeguards which are capable of holding states accountable for insufficient human rights protections through robust judicial review even, and perhaps especially, in highly charged cases that concern national security.